PARTISIPASI DALAM PENGGANGGARAN DAN PRESTASI MANAJER: PENGARUH KOMITMEN ORGANISASI DAN INFORMASI JOB-RELEVANT - Margareta Diana Pangastuti; I Komang Arthana (Jurnal Riset Akuntansi (JUARA), 2018)
Some previous studies stated that he relationship between budgetary participation and managers’ performance was positive and significant, and the others confirmed otherwise. Inserting intervening or moderating variables in that relationship, could solve the difference. This research analyzes the influence of participation budget arrangement on the managers’ performance, in which the organizational commitment and job-relevant information is treated as the intervening variable. There in the direct, positive, and significant influence of the participation on the managers performance. The more intense the budgetary participation, the higher his/her work performance will be. Moreover, when the organizational commitment and job-relevant information are the intervening variables, the recent influence of the participation on he manager’s performance become weaker. This indicates that the strength of that influence is indirect, through the organizational commitment and job relevant information.